Contemporary cultures 1600 to the present (McGraw-Hill networks, 2014)
8 Chapters in this edition are: Chapter 1: What Does a Historian Do? Chapter 2: Studying Geography, Economics, and Citizenship Chapter 3: Age of Exploration and Trade Chapter 4: The Scientific Revolution and Enlightenment Chapter 5: Political and Industrial Revolutions Chapter 6: Imperialism and WW I Chapter 7: WW II and the Cold War Chapter 8: Building Today's World